Static and dynamic impacts of six-phase power transmission system - Ahmad, Mohd. Redzuan (2007)
Electricity is considered as the driving force for a country, which is undergoing rapid industrialization. Constraints on the availability of land and planning permission for overhead transmission lines have renewed interest in techniques to increase the power carrying capacity of existing Right-Of-Ways (ROW). Six-phase (6-F) transmission appears to be the most promising solution to the need to increase the capability of existing transmission lines and at the same time, respond to the concerns related to electromagnetic fields. One of the main advantages of 6-F transmission is that a 6-F line can carry up to 73% more electric power than a three-phase (3-F) double-circuit line on the same transmission ROW. However, this conversion will have impacts on the power system operations. This thesis presents the static and dynamic impacts of 6-F transmission system. The study initially involved the development of 6-F transmission system model from the 3-F transmission line. The models were developed using the Power System Computer Aided Design/Electromagnetic Transient and Direct Current (PSCAD/EMTDC). In this research, the load flow studies, fault analysis and transient stability were conducted on the IEEE Test Systems and 19-Bus TNB South Kelantan Equivalent System. These studies were performed in sufficient detail to determine how the 6-F conversion will affect steady state operation, fault current duties, and system stability. A laboratory prototype of Kuala Krai to Gua Musang, Kelantan TNB Thevenin equivalent systems was developed to validate the simulation results. From the simulation results, it has been shown that the IEEE Test Systems and 19-Bus TNB South Kelantan Equivalent System with 6-F single-circuit transmission has better stability limits compared to the 3-F double-circuit transmission. It is shown that the voltage level at all buses remains within acceptable limit. It is also discovered that the fault current magnitude of the 6-F single-circuit transmission is less as compared to the 3-F double-circuit transmission.